Achievement of competencies of the students of BRAC non-formal primary schools, 2000-2002 - Nath, Samir R. (© Educational Research Unit, RED, BRAC, 2016)
1. Introduction 2. Objective 3. Methodology 4. Findings: Achievement of Bangla, English, Mathematics, Social studies competencies, Overall learning achievement. 5. Highlights of the findings.